Hubungan Fungsi Seksual Terhadap Kualitas Hidup Pada Wanita Post Histerektomi Di SMC RS Telogorejo - Endah Kristiani; Rinda Intan Sari; Dwi Fitriyanti (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2023)
Hysterectomy has become a separate concern for patient, many women describe their post-hysterectomy sexual life as influenced by relationship problems for quality oflife and sexual relationship with her partner. It is undeniable that women's sexual function is an important component of quality of life and activities of daily living. This study aims to determine the relationship between sexual function and quality of life in post-hysterectomy women. This type of research is a quantitative research within 46 sample. The sampling technique in this study was by Consecutive Sampling, at April 28 – June 2 2023. The results of the study state 41-50 years old majority (52,1%), work (89,1%) and higher education (71,1%). Based on the results of the spearman rank test obtained a p-value of 0.147or > 0.05, meaning that there was no relationship between sexual function and quality of life in post-hysterectomy patients. Suggest:For next researcher recommended to analysis the age specially is Pnemenopouse.